THE RELATIONSHIP BETWEEN sTREM-1 AND ACTIVATION OF INFLAMMATORY BOWEL DISEASES - Yasin Kutlu; İlkim Deniz Toprak; Yasemin Gökden; Hasan Eruzun; Yücel Arman; Şengül Aydın Yoldemir; Zeki Toprak; Tufan Tükek (İstanbul Tıp Fakültesi Dergisi)
Objective: In inflammatory bowel disease (IBD), there is no reliable biomarker, yet. We aimed to determine whether Serum Soluble Triggering Receptor Expressed on Myeloid Cells-1 (sTREM-1) could be useful as a marker for the diagnosis and/or the determination of disease activity in patients with IBD. Material and Method: A total of 47 patients with ulcerative colitis (UC) and 25 patients with Crohn’s disease (CD) were prospectively enrolled. Clinical disease activity was analyzed using the Crohn’s Disease Activity Index (CDAI) for CD and the Truelove-Witts index for UC. Results: sTREM-1 levels were significantly lower in patients with IBD compared to healthy controls (p=0.001). In comparison of the levels of sTREM-1 between the different groups (CD, UC, and healthy controls) the difference was statistically significant. No considerable differences in sTREM-1 levels were determined in patients with active versus quiescent disease. The sTREM-1 levels negatively correlated with C-reactive protein, blood neutrophil-lymphocyte ratio, and positively with haemoglobin levels. Conclusion: sTREM-1 levels are decreased in IBD patients compared with the healthy individuals. It may, therefore, be useful for the diagnosis of IBD. However, it does not seem to be a precise marker of disease activity in IBD and cannot be suggested for assessing disease activity in these patients.